Advances in government enterprise architecture - Saha, Pallab, 1970- (Hershey PA : Information Science Reference, 2009)
'This book is a compilation of chapters on government Enterprise architecture with the intention of informing professionals with different levels of enterprise architecture knowledge'--Provided by publisher.
'Premier reference source'--Cover.
Description based on print version record.
Includes bibliographical references (p. 438-462) and index.
Keywords: Internet in public administration; Public administration; Management; Information technology; Management information systems; Computer architecture; Electronic books; Electronic books